The Mediating Role of Innovation Performance Between Social Media Capability and Business Sustainability in E-Business - Setya, Kevin Ganda; Agustinus, Michael; Sugiyanto, Michael Putra; Hidayat, Desman (Milestone: Journal of Strategic Management, 2021)
The purpose of this study is to find out and analyze the factors of social media capability impact on business sustainability during Covid-19 pandemic. This survey is taken from Jakarta online SMEs. This research is using a quantitative approach method and uses 101 samples. In analyzing data, we use Structural Equation Model (SEM) by using SmartPLS application. Our result shows that social media capability does not have an impact directly on business sustainability but has an impact indirectly mediated by innovation performance. This study suggests that online SMEs should take the advantage of social media capability and make an innovation for their products/services to make their business sustainable.